Method for preparing fused quartz powder material
Through a method including slurry adjustment, flotation, pickling, drying and secondary heat treatment, the problem of poor high temperature resistance and density of products in the existing fused silica powder process has been solved, and the purity of the powder is significantly improved and The service life has improved the product quality.
Patent Information
- Application Number
- CN202411818228.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-02-14
AI Technical Summary
The existing process for making fused silica powders takes a lot of time, the product has poor high temperature resistance and density, short service life, high impurity content of powders, insufficient purity, which affects product quality.
A method for preparing fused silica powder material is adopted, including slurry adjustment, flotation machine rough selection, circulating pickling, drying treatment and secondary heat treatment, and the powder slurry concentration is adjusted through nanocarbon black and silicon carbide powder. Use mixed acid solution for pickling, pass active gas and water vapor for flotation, ultrasonic cleaning and multiple water washing, and finally react and sintering in a high-temperature carbon tube furnace to obtain high-purity fused silica powder.
It significantly improves the purity and density of fused silica powder, extends the service life of the product, reduces the impurity content, and improves the high temperature resistance and quality of the product.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of quartz powder processing, in particular to a method for preparing fused quartz powder material. Background Art
[0002] Fused quartz is made by melting natural high-purity silicon dioxide in an electric furnace at a temperature above 1760°C and then rapidly cooling it. This process converts crystalline silicon dioxide into an amorphous glass melt. The melting temperature of fused quartz is about 1713°C, the thermal conductivity is low, and the thermal expansion coefficient is almost the smallest among all refractory materials, so it has extremely high thermal shock stability. Therefore, during the roasting and pouring process, the fused quartz shell rarely breaks due to temperature changes. It is an ideal refractory material for investment casting. It can be used as a refractory material for surface or back layer coatings, as well as a sanding material. Fused quartz will partially or fully improve the performance of the shell. The small thermal expansion coefficient of fused quartz is conducive to preventing the shell from cracking and deforming during the dewaxing and roasting process, and is conducive to ensuring the dimensional stability of the casting. Fused quartz has high purity and good stability of the coating; the shell has improved high-temperature creep resistance. The thermal conductivity of fused quartz is poor at low temperatures, and its heat capacity is small, only half of that of zircon sand. Most metal liquids have poor wettability to it, which makes it easy to have a gap between the metal solidification layer and the inner surface of the shell, and the thermal conductivity is further reduced, which is conducive to the filling of thin-walled castings. At high temperatures, fused quartz has high transparency and can transfer heat through radiation, making its thermal conductivity exceed that of aluminum silicate shells. This makes the casting cool faster and it is easier to obtain a sound casting.
[0003] The existing process for making fused quartz powder is time-consuming, and the product has poor high temperature resistance and density, a short service life, a high impurity content in the powder, and insufficient purity, which affects product quality. This has become a problem we need to solve. Summary of the invention
[0004] The present invention aims at the existing process for preparing fused quartz powder in the background technology, which is time-consuming to prepare, and the product has poor high temperature resistance and density, short service life, high impurity content of the powder, insufficient purity, and affects product quality. A method for preparing fused quartz powder material is provided.
[0005] In order to solve the above-mentioned problem, the present invention adopts the following modified technical scheme, a method for preparing fused quartz powder material, the specific preparation method comprises the following steps, S1, slurry preparation: adding ultrafine fused quartz powder into a roughing slurry preparation barrel, adding nano carbon black and silicon carbide powder to adjust the powder slurry concentration to 28%-45%, adding acid, adjusting the pH value to 6.3, and obtaining fused quartz powder slurry;
[0006] S2, roughing by flotation machine: pump the fused quartz powder slurry in the roughing slurry mixing barrel into the flotation tank of the flotation machine through the slurry pump, add the impurity removal mixture, stir for 15 minutes, add the frother, stir for another 10 minutes, open the flotation machine inflation valve and start scraping the foam, scraping the foam for 25 minutes;
[0007] S3, cyclic pickling, followed by water washing for full treatment; then sent to an ultrasonic cleaning machine for 4-6 ultrasonic cleanings, and then dehydrated by multiple washings with deionized water or electronic grade pure water;
[0008] S4, drying treatment: the dehydrated fused quartz powder is sent into a heat treatment tank, and filled with inert gas, and the ventilation device is turned on to circulate the protective gas in the container;
[0009] S5, secondary heat treatment, in a high temperature carbon tube furnace, the temperature is raised to 1500°C at a heating rate of 5°C / min and sintered for 30 minutes, and the product is obtained by cooling.
[0010] As a further preferred embodiment of the present invention, in step S1, pickling is performed using a mixed acid solution, which is a mixture of hydrofluoric acid and nitric acid in a ratio of 1:0.8.
[0011] As a further preferred embodiment of the present invention, in step S2, during the flotation process, Cl2 or other active gases are introduced simultaneously, and the amount of active gas is controlled at 0.3 m 3 / min, and active gas was introduced every 5min for 15min.
[0012] As a further preferred embodiment of the present invention, in step S2, during the flotation process, water vapor is continuously injected, and the heating rate in the temperature range of 55 to 65°C is controlled to inject water vapor, the temperature is increased by 5°C every 0.5h, and the heating rate in the temperature range of 75 to 85°C is 1°C per hour. The heating temperature is controlled at 95°C for 2-4h.
[0013] As a further preferred embodiment of the present invention, in step S3, the pickling method includes: acid preparation: oxalic acid and quartz sand are added to the pickling fluidized bed reactor together, hydrofluoric acid is directly pumped from the hydrofluoric acid storage tank into the acid circulation tank for replenishment, and the prepared acid solution is pumped from the acid circulation tank into the dedicated distribution device below the pickling fluidized bed reactor through a pipeline by an acid-resistant pump; pickling: the prepared acid solution overflows from the upper part, is filtered through a 200-mesh filter, and is returned to the acid circulation tank, and this operation is repeated. The pickling fluidized bed reactor has an operating temperature of 65°C and is heated and ventilated. The acid solution is subjected to dynamic reaction for 3-6 hours through the steam network through a graphite heat exchanger. The oxalic acid concentration in the pickling solution of oxalic acid and hydrofluoric acid used in the high-purity quartz sand pickling section is 10%, and the HF acid concentration is 1%. Deacidification: After the pickling of the raw quartz sand is completed, it is pumped out through a pump and sent to a vibrating screen through a pipeline to remove the acid solution. Purification: The dilute acid solution flows into the intermediate storage tank by gravity and is quantitatively sent to the acid purifier for purification. The concentrated acid solution returns to the acid circulation tank for continued use, and the circulating dilute acid solution continues to return to the pipeline to dilute the acid solution extracted from the pickling fluidized bed.
[0014] As a further preferred embodiment of the present invention, in step S4, the inert gas is one of helium, neon and argon.
[0015] As a further preferred embodiment of the present invention, in step S5, the high-temperature carbon tube furnace is heated to 200°C at a heating rate of 10°C / min, heated to 400°C at a heating rate of 5°C / min, heated to 800°C at a heating rate of 2°C / min, kept warm for 60 minutes, and finally heated to 1500°C for 1.5 hours.
[0016] The beneficial effects of the present invention are as follows: the present invention mainly removes metal minerals such as iron and aluminum contained in impurity minerals, and can also remove non-volatile metal impurities by generating volatile compounds, and the obtained quartz powder has a higher purity. DETAILED DESCRIPTION
[0017] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0018] The present invention provides a technical solution: a method for preparing a fused quartz powder material, the specific preparation method comprises the following steps, S1, slurry preparation: adding ultrafine fused quartz powder into a roughing slurry preparation barrel, adding nano carbon black and silicon carbide powder to adjust the powder slurry concentration to 28%-45%, adding acid, adjusting the pH value to 6.3, and obtaining a fused quartz powder slurry;
[0019] S2, roughing by flotation machine: pump the fused quartz powder slurry in the roughing slurry mixing barrel into the flotation tank of the flotation machine through the slurry pump, add the impurity removal mixture, stir for 15 minutes, add the frother, stir for another 10 minutes, open the flotation machine inflation valve and start scraping the foam, scraping the foam for 25 minutes;
[0020] S3, cyclic pickling, followed by water washing for full treatment; then sent to an ultrasonic cleaning machine for 4-6 ultrasonic cleanings, and then dehydrated by multiple washings with deionized water or electronic grade pure water;
[0021] S4, drying treatment: the dehydrated fused quartz powder is sent into a heat treatment tank, and filled with inert gas, and the ventilation device is turned on to circulate the protective gas in the container;
[0022] S5, secondary heat treatment, in a high temperature carbon tube furnace, the temperature is raised to 1500°C at a heating rate of 5°C / min and sintered for 30 minutes, and the product is obtained by cooling.
[0023] In step S1, pickling is performed using a mixed acid solution, which is a mixture of hydrofluoric acid and nitric acid in a ratio of 1:0.8.
[0024] In step S2, during the flotation process, Cl2 or other active gases are introduced at the same time, and the amount of active gas is controlled at 0.3m 3 / min, and active gas was introduced every 5min for 15min.
[0025] In step S2, during the flotation process, water vapor is continuously injected, and the heating rate in the temperature range of 55-65°C is controlled to inject water vapor, the temperature is increased by 5°C every 0.5h, and the heating rate in the temperature range of 75-85°C is 1°C per hour. The heating temperature is controlled at 95°C for 2-4h.
[0026] In step S3, the pickling method includes: acid preparation: oxalic acid and quartz sand are added to the pickling fluidized bed reactor together, hydrofluoric acid is directly pumped from the hydrofluoric acid storage tank into the acid circulation tank for replenishment, and the prepared acid solution is pumped from the acid circulation tank into the special distribution device below the pickling fluidized bed reactor through a pipeline by an acid-resistant pump, pickling: the prepared acid solution overflows from the upper part, is filtered through a 200-mesh filter, and is returned to the acid circulation tank, and this operation is repeated. The pickling fluidized bed reactor has an operating temperature of 65°C and is heated through the steam network. The graphite heat exchanger conducts a dynamic reaction on the acid solution for 3-6 hours. The oxalic acid concentration in the oxalic acid and hydrofluoric acid pickling solution used in the high-purity quartz sand pickling section is 10%, and the HF acid concentration is 1%. Deacidification: After the raw quartz sand is pickled, it is pumped out through a pump and sent to a vibrating screen through a pipeline to remove the acid solution. Purification: The dilute acid solution flows into the intermediate storage tank by gravity and is quantitatively sent to the acid purifier for purification. The concentrated acid solution returns to the acid circulation tank for continued use, and the circulating dilute acid solution continues to return to the pipeline to dilute the acid solution extracted from the pickling fluidized bed.
[0027] In step S4, the inert gas is one of helium, neon and argon.
[0028] In step S5, the high temperature carbon tube furnace is heated to 200°C at a heating rate of 10°C / min, heated to 400°C at a heating rate of 5°C / min, heated to 800°C at a heating rate of 2°C / min, kept warm for 60 minutes, and finally heated to 1500°C for 1.5 hours.
[0029] Embodiment 1
[0030] A method for preparing a fused quartz powder material, the specific preparation method comprises the following steps, S1, slurry preparation: adding ultrafine fused quartz powder into a roughing slurry preparation barrel, adding nano carbon black and silicon carbide powder to adjust the powder slurry concentration to 45%, adding acid, acid washing using a mixed acid solution, the mixed acid solution is a mixture of hydrofluoric acid and nitric acid, the ratio is 1:0.8, adjusting the pH value to 6.3, and obtaining a fused quartz powder slurry;
[0031] Flotation machine roughing: The fused quartz powder slurry in the roughing slurry tank is pumped into the flotation tank of the flotation machine through a slurry pump, and a decontamination agent is added. During the flotation process, Cl2 or other active gases are introduced at the same time, and the amount of active gas is controlled at 0.3m 3 / min, introduce active gas for 15min every 5min, add frother after stirring for 15min, stir for another 10min, open the flotation machine inflation valve to start scraping bubbles, scraping bubbles for 25min, during the flotation process, continuously inject water vapor, control the heating rate of the temperature range of 65℃ to inject water vapor, increase the temperature by 5℃ every 0.5h, and the heating rate of the temperature range of 85℃ is 1℃ per hour, the heating temperature is controlled at 95℃, and it lasts for 4h;
[0032] Circulating pickling, the pickling method includes, acid preparation: oxalic acid and quartz sand are added to the pickling fluidized bed reactor together, hydrofluoric acid is directly pumped from the hydrofluoric acid storage tank into the acid circulation tank for replenishment, and the prepared acid solution is pumped from the acid circulation tank into the special distribution device below the pickling fluidized bed reactor through a pipeline by an acid-resistant pump, pickling: the prepared acid solution overflows from the upper part, is filtered through a 200-mesh filter, and returned to the acid circulation tank, and this operation is repeated. The working temperature of the pickling fluidized bed reactor is 65°C, and the acid solution is heated through the steam pipe network through a graphite heat exchanger, and the dynamic reaction is 6 hours, and high-purity quartz sand pickling The oxalic acid concentration in the oxalic acid and hydrofluoric acid pickling solution used in the process section is 10%, and the HF acid concentration is 1%. Deacidification: After the raw quartz sand is pickled, it is pumped out through a pump and sent to a vibrating screen through a pipeline to remove the acid solution. Purification: The dilute acid solution flows into the intermediate storage tank by gravity and is quantitatively sent to the acid purifier for purification. The concentrated acid solution returns to the acid circulation tank for continued use. The circulating dilute acid solution continues to return to the pipeline to dilute the acid solution extracted from the pickling fluidized bed. After pickling, it is washed with water for full treatment; it is then sent to an ultrasonic cleaning machine for 6 ultrasonic cleanings, and then deionized water or electronic grade pure water is used for multiple washings and dehydration;
[0033] Drying treatment: The dehydrated fused quartz powder is sent into a heat treatment tank and filled with inert gas, which is helium. At the same time, the ventilation device is turned on to circulate the protective gas in the container;
[0034] For the secondary heat treatment, in a high-temperature carbon tube furnace, the reaction sintering was carried out at 1500°C at a heating rate of 5°C / min for 30 minutes. In the high-temperature carbon tube furnace, under vacuum, the temperature was heated to 200°C at a heating rate of 10°C / min, then to 400°C at a heating rate of 5°C / min, and then to 800°C at a heating rate of 2°C / min, and the temperature was kept for 60 minutes. Finally, the temperature was heated to 1500°C for 1.5 hours, and the product was obtained by cooling.
[0035] Embodiment 2
[0036] A method for preparing a fused quartz powder material, the specific preparation method comprises the following steps, S1, slurry preparation: adding ultrafine fused quartz powder into a roughing slurry preparation barrel, adding nano carbon black and silicon carbide powder to adjust the powder slurry concentration to 28%, adding acid, acid washing using a mixed acid solution, the mixed acid solution is a mixture of hydrofluoric acid and nitric acid, the ratio is 1:0.8, adjusting the pH value to 6.3, and obtaining a fused quartz powder slurry;
[0037] Flotation machine roughing: The fused quartz powder slurry in the roughing slurry tank is pumped into the flotation tank of the flotation machine through a slurry pump, and a decontamination agent is added. During the flotation process, Cl2 or other active gases are introduced at the same time, and the amount of active gas is controlled at 0.3m 3 / min, introduce active gas for 15min every 5min, add frother after stirring for 15min, and then open the flotation machine inflation valve to start scraping bubbles after stirring for 10min, and scrape bubbles for 25min. During the flotation process, water vapor is continuously injected, and the heating rate of the temperature range of 55℃ is controlled to inject water vapor, and the temperature is increased by 5℃ every 0.5h. The heating rate of the temperature range of 75℃ is 1℃ per hour, and the heating temperature is controlled at 95℃ for 2h;
[0038] Circulating pickling, the pickling method includes, acid preparation: oxalic acid and quartz sand are added to the pickling fluidized bed reactor together, hydrofluoric acid is directly pumped from the hydrofluoric acid storage tank into the acid circulation tank for replenishment, and the prepared acid solution is pumped from the acid circulation tank into the special distribution device below the pickling fluidized bed reactor through a pipeline by an acid-resistant pump, pickling: the prepared acid solution overflows from the upper part, is filtered through a 200-mesh filter, and returned to the acid circulation tank, and this operation is repeated. The pickling fluidized bed reactor has an operating temperature of 65°C, and the acid solution is heated through a steam pipe network through a graphite heat exchanger, and the dynamic reaction is 3 hours, and high-purity quartz sand pickling The oxalic acid concentration in the oxalic acid and hydrofluoric acid pickling solution used in the process section is 10%, and the HF acid concentration is 1%. Deacidification: After the raw quartz sand is pickled, it is pumped out through a pump and sent to a vibrating screen through a pipeline to remove the acid solution. Purification: The dilute acid solution flows into the intermediate storage tank by gravity and is quantitatively sent to the acid purifier for purification. The concentrated acid solution returns to the acid circulation tank for continued use. The circulating dilute acid solution continues to return to the pipeline to dilute the acid solution extracted from the pickling fluidized bed. After pickling, it is washed with water for full treatment; it is then sent to an ultrasonic cleaning machine for 4 ultrasonic cleanings, and then deionized water or electronic grade pure water is used for multiple washings and dehydration;
[0039] Drying treatment: The dehydrated fused quartz powder is sent into a heat treatment tank and filled with inert gas, which is neon. At the same time, the ventilation device is turned on to circulate the protective gas in the container;
[0040] For the secondary heat treatment, in a high-temperature carbon tube furnace, the reaction sintering was carried out at 1500°C at a heating rate of 5°C / min for 30 minutes. In the high-temperature carbon tube furnace, under vacuum, the temperature was heated to 200°C at a heating rate of 10°C / min, then to 400°C at a heating rate of 5°C / min, and then to 800°C at a heating rate of 2°C / min, and the temperature was kept for 60 minutes. Finally, the temperature was heated to 1500°C for 1.5 hours, and the product was obtained by cooling.
[0041] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It is obvious to those skilled in the art that the present invention is not limited to the details of the above exemplary embodiments, and the present invention can be implemented in other specific forms without departing from the spirit or basic features of the present invention. Therefore, no matter from which point of view, the embodiments should be regarded as exemplary and non-restrictive. The scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes that fall within the meaning and scope of the equivalent elements of the claims are included in the present invention.
[0042] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A method for preparing a fused silica powder material, characterized in that: The specific preparation method comprises the following steps: S1, slurry preparation: adding ultrafine fused quartz powder into a roughing slurry preparation barrel, adding nano carbon black and silicon carbide powder to adjust the powder slurry concentration to 28%-45%, adding acid, adjusting the pH value to 6.3, and obtaining fused quartz powder slurry; S2, roughing by flotation machine: pump the fused quartz powder slurry in the roughing slurry mixing barrel into the flotation tank of the flotation machine through the slurry pump, add the impurity removal mixture, stir for 15 minutes, add the frother, stir for another 10 minutes, open the flotation machine inflation valve and start scraping the foam, scraping the foam for 25 minutes; S3, cyclic pickling, followed by water washing for full treatment; then sent to an ultrasonic cleaning machine for 4-6 ultrasonic cleanings, and then dehydrated by multiple washings with deionized water or electronic grade pure water; S4, drying treatment: the dehydrated fused quartz powder is sent into a heat treatment tank, and filled with inert gas, and the ventilation device is turned on to circulate the protective gas in the container; S5, secondary heat treatment: in a high temperature carbon tube furnace, the temperature is raised to 1500°C at a heating rate of 5°C / min and sintered for 30 minutes, and the product is obtained by cooling.
2. A method for preparing fused silica powder material according to claim 1, characterized in that: In step S1, pickling is performed using a mixed acid solution, which is a mixture of hydrofluoric acid and nitric acid in a ratio of 1:0.
8.
3. A method for preparing fused silica powder material according to claim 1, characterized in that: In step S2, during the flotation process, Cl2 or other active gases are introduced at the same time, and the amount of active gas is controlled at 0.3m 3 / min, and active gas was introduced every 5min for 15min.
4. A method for preparing fused silica powder material according to claim 1, characterized in that: In step S2, during the flotation process, water vapor is continuously injected, and the heating rate in the temperature range of 55-65°C is controlled to inject water vapor, the temperature is increased by 5°C every 0.5h, and the heating rate in the temperature range of 75-85°C is 1°C per hour. The heating temperature is controlled at 95°C for 2-4h.
5. The method for preparing fused silica powder material according to claim 1, characterized in that: In step S3, the pickling method includes: acid preparation: oxalic acid and quartz sand are added to the pickling fluidized bed reactor together, hydrofluoric acid is directly pumped from the hydrofluoric acid storage tank into the acid circulation tank for replenishment, and the prepared acid solution is pumped from the acid circulation tank into the special distribution device below the pickling fluidized bed reactor through a pipeline by an acid-resistant pump, pickling: the prepared acid solution overflows from the upper part, is filtered through a 200-mesh filter, and is returned to the acid circulation tank, and this operation is repeated. The pickling fluidized bed reactor has an operating temperature of 65°C and is heated through the steam network. The graphite heat exchanger conducts a dynamic reaction on the acid solution for 3-6 hours. The oxalic acid concentration in the oxalic acid and hydrofluoric acid pickling solution used in the high-purity quartz sand pickling section is 10%, and the HF acid concentration is 1%. Deacidification: After the raw quartz sand is pickled, it is pumped out through a pump and sent to a vibrating screen through a pipeline to remove the acid solution. Purification: The dilute acid solution flows into the intermediate storage tank by gravity and is quantitatively sent to the acid purifier for purification. The concentrated acid solution returns to the acid circulation tank for continued use, and the circulating dilute acid solution continues to return to the pipeline to dilute the acid solution extracted from the pickling fluidized bed.
6. A method for preparing fused silica powder material according to claim 1, characterized in that: In step S4, the inert gas is one of helium, neon and argon.
7. A method for preparing fused silica powder material according to claim 1, characterized in that: In step S5, the high temperature carbon tube furnace is heated to 200°C at a heating rate of 10°C / min, heated to 400°C at a heating rate of 5°C / min, heated to 800°C at a heating rate of 2°C / min, kept warm for 60 minutes, and finally heated to 1500°C for 1.5 hours.
Citation Information
Cited By
High-temperature phase stable fused quartz refractory material and preparation method thereof
CN120157465A